Comparative analysis of the medicinal plant Polygonatum kingianum (Asparagaceae) with related verticillate leaf types of the Polygonatum species based on chloroplast genomes - Shi, Naixing; Yang, Zefen; Miao, Ke; Tang, Lilei; Zhou, Nian; Xie, Pingxuan; Wen, Guosong (Frontiers in Plant Science, 2023)
Background: Polygonatum kingianum has been widely used as a traditional Chinese medicine as well as a healthy food. Because of its highly variable morphology, this medicinal plant P. kingianum, often failed to distinguish it from other related verticillate leaf types of Polygonatum species. The contaminants in the P. kingianum products not only decrease the products’ quality but also threaten the consumer safety, which seriously inhibits the industrial application of P. kingianum. Methods: Nine complete chloroplast (cp) genomes of six verticillate leaf types of Polygonatum species were de novo assembled and systematically analyzed. Results: The total lengths of newly sequenced cp genomes ranged from 155,437 to 155,977 bp, including 86/87 protein-coding, 38 tRNA and 8 rRNA genes which all exhibited well-conserved genomic structures and gene orders. The differences in the IR/SC (inverted repeats/single-copy) boundary regions and simple sequence repeats were detected among the verticillate leaf types of the Polygonatum cp genomes. Comparative cp genomes analyses revealed that a higher similarity was conserved in the IR regions than in the SC regions. In addition, eleven divergent hotspot regions were selected, providing potential molecular markers for the identification of the Polygonatum species with verticillate leaf types. Phylogenetic analysis indicated that, as a super barcode, plastids realized a fast and efficient identification that clearly characterizing the relationships within the verticillate leaf type of Polygonatum species. In brief, our results not only enrich the data on the cp genomes of the genus Polygonatum, but also provide references for the P. kingianum germplasm resource protection, herbal cultivation and drug production. Conclusion: This study not only accurately identifies P. kingianum species, but also provides valuable information for the development of molecular markers and phylogenetic analyses of the Polygonatum species with verticillate leaf types.